THE SOCIAL AND EDUCATIONAL PROJECTING IN THE SPIRITUAL AND MORAL FORMATION OF THE FUTURE TEACHER - Pavel Aleksandrovich Kislyakov; Elena Alexandrovna Shmeleva (Sovremennye Issledovaniâ Socialʹnyh Problem, 2015)
The article reveals the potential of socio-educational design in the spiritual and moral formation of future teachers. It shows the necessity of using the traditions of Orthodox culture and pedagogy in preparing students to create the conditions of spiritual and moral development of pupils in school and extracurricular activities. It describes the socio-educational pro-ject for students «Orthodoxy – the way to spiritual safety of a Russian person and the Russian people». The project includes teaching students the history of Orthodox pedagogy, seminars «Word of Pastor and Teacher», cultural and educational tours of the orthodox monasteries, volunteer action «Mercy» for children in difficult situations. Socio-educational design allows you to form students’ social activity, general cultural and professional competence in the field of spiritual and moral development of pupils.